THE POLICY OF FINANCIAL CONSOLIDATION AND ECONOMIC DEVELOPMENT IN THE FACE OF EXTERNAL SHOCKS - I. S. Bukina (Финансы: теория и практика)
Topic. The article discusses the policy of progressive fiscal consolidation carried out in developed countries and in Russia. There is also a characteristic of fiscal policy in Russia. Purpose. We aim to identify the actual effects of the policy of financial consolidation in terms of a tight dependence on the cyclical development of the world economy.Methodology. We used the methodology of macroeconomic analysis, systemic approach, statistical methods (cluster analysis), and methods of mathematical statistics and econometrics.Results. The rising debt of the developed countries in conditions of chronic budget deficit actualized the task of fiscal consolidation. Initially, the idea of fiscal consolidation was to implement a progressive consolidation, i. e. the reduction of budget expenditures, which would contribute to the formation of the financial potential. In turn, the financial potential is realized in the form of a budget surplus that could be used to reduce the tax burden and rise of spending in the future. Literature indicates on the effect of reproduction of the austerity measures due to changes in budget institutions; it limits the ability to stimulate the economy through measures of fiscal policy. Thus, the approach to the implementation of fiscal policy is offset, in the direction of tightening. The analysis of fiscal policy in Russia since the late 1990s does not allow concluding that its character corresponds to the ideas of progressive fiscal consolidation. Despite the creation of a significant budget surplus in times of boom, it practically was not used for the task of stimulating economic development.Conclusions. The policy of fiscal consolidation, ongoing in Russia, primarily aimed at solving a narrow range of budget issues and is not intended for the future to stimulate the economy.